Expression of bone morphogenetic protein-2 after using chitosan gel with different molecular weight on wound healing process of dental extraction - Sularsih Sularsih; Endah Wahjuningsih (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Bone morphogenetic protein-2 (BMP-2) is bone stimulator which capable of inducing differentiation of mesenchymal cells into osteoblast, stimulating bone formation in wound healing process of dental extraction. Chitosan is polymer composed N-acetylD-glucosamine unit that has been used in various applications in wound healing process and bone tissue engineering. Purpose: The objective of this research was to analyzed expressions of BMP-2 for 7,14 and 21 days after using chitosan gel with different molecular weight on wound healing process of dental extraction. Method: The research was an experimental laboratory study. Rattus nornegicus strain wistar male, aged 8-16 weeks, divided into 3 treatment groups namely group 1 and II which given chitosan gel 1 % with high and low molecular weight and group III as control which were not given chitosan gel. Chitosan gel were applied into the socket of dental extraction. Rat was decaputated 7,14 and 21 days after chitosan gel application and the jaw in the treated regions and control group were cut for immunohistochemical examination to observe BMP-2. Data were analyzed using ANOVA test. Result: The result of this research showed significant differences on BMP-2 for 7,14 and 21 days observation (p<0,05). The increasing of BMP-2 were found in the group which given chitosan gel with high molecular weight. Conclusion: It may be concluded that chitosan gel with high molecular weight can enhance the expresion of BMP-2 on wound healing process ofdental extraction.